Modern culture and practice of the urban water landscape design: Theoretical and practical explorations - Yue, Zixuan (Вестник Томского государственного университета. Культурология и искусствоведение)
This paper aims to deeply understand the impact of modern culture on the urban water landscape design and explore innovations and applications in practice. Firstly, through the analysis of cultural theory, the important role and influence of modern culture on water landscape design in urban environment are revealed. Secondly, the relevant concepts and principles of water landscape art design practice, as well as their integration with modern cultural theory, are discussed. Furthermore, through case analysis, the application and innovative methods of modern culture in water landscape art design practice are summarized. Finally, suggestions for further research and development are proposed to promote the integration of modern culture and water landscape art design practice, and to drive greater development of water landscape art design in modern society. Theoretical significance of our research demonstrates characteristics and trends of cultural development in modern society and provide a theoretical foundation for further promoting the organic integration of modern culture, art and design. Practical significance implies that integrating modern culture into water landscape art design can align designs more closely with social needs and individual perceptions, enhance the quality of public spaces, and foster artistic experiences and aesthetic enjoyment. Social significance implies that integration of modern culture into water landscape design can strengthen the cultural atmosphere and humanistic characteristics of cities and improve the quality of urban life. Since modern culture is characterized by its openness, diversity, dynamism, and trendiness, and it has had a profound impact on the fields of art and design. For our research purposes we summarized some crucial aspects as following: reflection on tradition and innovative consciousness, emphasis on the individual and social relations, emphasis on expression and communication. emphasis on social critique and zeitgeist. The case analysis presented in the paper include urban park water landscape design, water landscape design of waterfront leisure area, city square water landscape design and also analysis of the role of water landscape design in cultural heritage and innovation.